Trends in maternal mortality in a tertiary care hospital - Mohana Sundari, K. P.; Dheeba Jayanthi, R.; Ramasamy, Bharathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: To analyze the trends in maternal mortality in a tertiary hospital in Salem, Tamil Nadu. Methods: Design of the study was retrospective. Records of all maternal deaths occurring for the past 3 years from January 2013-December 2015 were studied and various factors analyzed and compared. Results: The maternal mortality rate ranged between 559-802/ 1,00,000 live births in our study. The majority of deaths were in the age group between 21-25 yrs. The majority of deaths in 2013 were due to hemorrhage (19.5%) followed by cortical venous thrombosis (17.6%), hypertensive disorders (14.6%). But in 2014 and 2015 hypertensive disorders were the common cause of death, [2014 (23%), 2015 (26.78%)] followed by hemorrhage (2014-12.8%, 2015 -17.5%) and sepsis (2014-20.5%, 2015-12.5%). Conclusions: Majority of maternal deaths can be prevented by adopting improved standards in early identification of preeclampsia, anemia and its management and early referral. Routine iron and folic acid supplementation to be done in an effective way. Proper antenatal care, emergency obstetrics care and routine audits are very much essential to decrease the maternal mortality as well as to know the trends of maternal deaths to develop subsequent management protocols.